Different synthetic pathways of nanoparticle‐cored dendrimers (NCDs): Effects on the properties and their application as redox active centers. Issue 22 (8th September 2014) - Paez, Julieta I.; Froimowicz, Pablo; Landfester, Katharina; Brunetti, Verónica; Strumia, Miriam
ABSTRACT The synthesis of nanoparticle‐cored dendrimers (NCDs) through surface functionalization of iron oxide nanoparticles (γ‐Fe2O3) by combining the conventional silane coupling agent 3‐(aminopropyl) triethoxysilane (APS) with dendritic moieties is studied and presented. Much emphasis has been put on the role played by each modifier and how they interact not only between themselves, but also with the dispersing media wherein the resulting NCDs are. As a part of the functionalization, redox‐active nitro groups were introduced onto the surface of each synthesized NCD thus making them electrochemically active. Then, the obtained NCDs were immobilized onto glassy carbon electrodes. Both the NCDs and modified electrodes are expected to be eventually exploited in analytical and sensing applications. © 2014 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2014, 52, 3185–3197